Controlled Environment Agriculture (CEA): A Promising Solution with Challenges in Tropical Zones - Choomjaihan Prasan; Onmankhong Jiraporn; Khwamphairn Bussaya; Sribua-iam Nattakan; Ninbua Metaporn; Subsomboon Ratchanon (BIO Web of Conferences)
In tropical greenhouses, single-stage direct evaporative cooling systems (DECS) are commonly employed. However, a key limitation of DECS is the inability to achieve desired temperature reductions. This study investigated and compared a two-stage pre-cooling system utilizing a heat exchanger in combining with DECS, against the traditional single-stage approach. The findings revealed a significant improvement in the two-stage system, achieving a 1.2°C lower in dry bulb temperature. Additionally, the magnitude of air condition change was 1.26 greater compared to the single-stage system. Furthermore, the two-stage system exhibited greater data consistency, indicating a more precise cooling effect.